Membranous nephropathy combined mild damage to kidney function of anti glomerular basement membrane disease - BAO Hong-mei; ZHANG Jian-chun; CHEN Xiao-ming; GUO Wen-gang; WANG Su-xia; ZHANG You-kang (Linchuang shenzangbing zazhi)
Objective The clinical manifestations,treatment methods,pathogenesis and prognosis of rare membranous nephropathy combined with anti glomerular basement membrane disease were discussed through 1 typical case analysis and literature review. Methods The pathological characteristics and clinical treatment of one cases of membranous nephropathy combined with anti glomerular basement membrane disease were retrospectively analyzed,and the related literature was reviewed. Results The patients were young men and past physical health,smoking history,Twenty days after infection appeared pulmonary hemorrhage,gross hematuria,large proteinuria,hypoproteinemia,edema,blood creatinine slight increase,anti GBM antibody positive renal pathology as membranous nephropathy with anti GBM disease with sub acute tubular interstitial nephropathy. Pre given methylprednisolone 0. 5 g/d. A total of four days,cyclophosphamide 0. 4 g/d,0. 6 g/d,continuous two days after shock treatment urinary protein was significantly reduced,the naked eye hematuria disappeared,but renal function and hemoglobin no improvement,also appear chest tightness,shortness of breath,activities after aggravating symptoms such as chest radiograph shows pulmonary blood increased,urine protein significantly reduced by eight double plasma exchange,with the hormone,cyclophosphamide,anti GBM antibody turn negative and pulmonary hemorrhage in complete control and renal function normal. Conclusions Membranous nephropathy combined with anti GBM disease is rare,clinical easy to misdiagnosis ormissed diagnosis,treatment is not timely prognosis is not good,especially with the rapid change of the patient’s condition. The diagnosis of clinical suspected as early as possible to anti GBM antibody or renal biopsy. The prognosis of patients with pulmonary hemorrhage,mild impairment of renal function by positive plasma exchange and hormone and cyclophosphamide therapy.